2009
DOI: 10.1038/leu.2009.171
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 by Nutlin-3a, an antagonist of MDM2, induces apoptosis and cellular senescence in adult T-cell leukemia cells

Abstract: It has been reported that the induction of cellular senescence through p53 activation is an effective strategy in tumor regression. Unfortunately, however, tumors including adult T-cell leukemia/lymphoma (ATL) have disadvantages such as p53 mutations and a lack of p16INK4a and/or p14 ARF. In this study we characterized Nutlin-3a-induced cell death in 16 leukemia/ lymphoma cell lines. Eight cell lines, including six ATL-related cell lines, had wild-type p53 and Nutlin-3a-activated p53, and the cell lines underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 57 publications
5
70
1
Order By: Relevance
“…43 Therefore, it is of interest to examine the effects of systemic upregulation of p53 on T cell function, as T cell mediated immune surveillance contributes to the control of tumors. In line with a previous study showing that nutlin-3 induces apoptosis in T cell leukemia cell lines, 44 we found that nutlin-3 induced apoptosis in activated T cells, and a corresponding increase in the expression of the pro-apoptotic protein Bax. In addition, and as shown here, nutlin-3 induced a massive increase in p21 and decrease in cMyc, changes that would contribute to cell cycle arrest.…”
Section: Discussionsupporting
confidence: 79%
“…43 Therefore, it is of interest to examine the effects of systemic upregulation of p53 on T cell function, as T cell mediated immune surveillance contributes to the control of tumors. In line with a previous study showing that nutlin-3 induces apoptosis in T cell leukemia cell lines, 44 we found that nutlin-3 induced apoptosis in activated T cells, and a corresponding increase in the expression of the pro-apoptotic protein Bax. In addition, and as shown here, nutlin-3 induced a massive increase in p21 and decrease in cMyc, changes that would contribute to cell cycle arrest.…”
Section: Discussionsupporting
confidence: 79%
“…Also a similar response has been described for T98G cells in response to temozolomide and etoposide [38]. TI-GAR-silenced U87MG and T98G cells showed a significant increase in SA-b-Gal activity, although in other models, such as T-cell leukemia cells, overexpression of TIGAR has been related with a decrease in apoptosis and increase in senescence [6]. Premature senescence has been described as an emerging anticancer response elicited by different stresses, ROS among them [39].…”
Section: Discussionmentioning
confidence: 75%
“…The importance of TIGAR as a regulator of oxidative stress is reflected in its capacity to modulate apoptosis, autophagy and senescence [1,5,6]. ROS regulate several cellular processes, although at higher levels they can induce genotoxic damage and cell death [7].…”
Section: Introductionmentioning
confidence: 99%
“…The combinatory use of TRAIL (tumor necrosis factor-related apoptosis-inducing ligand)-related drugs may be one of the most rational choices for Nutlin-3a based treatments. 141 Deguelin, naturally occurring rotenoid, showed a potent anti-proliferative effect on HTLV-1-transformed T-cells. 142 Curcumin, the major yellow pigment in turmeric, targeted Akt cell survival signaling pathway in HTLV-1-infected Tcell lines.…”
Section: ) Other Agents At Pre-clinical Stagementioning
confidence: 99%